Transformations of ferrates(iv, v, vi) in liquids: Mössbauer spectroscopy of frozen solutions. Issue 48 (28th November 2018) - Novak, Petr; Kolar, Michal; Machala, Libor; Siskova, Karolina M.; Karlicky, Frantisek; Petr, Martin; Zboril, Radek
Abstract : Two-step charge disproportionation mechanism of 3Fe(iv ) to 2Fe(iii ) and Fe(vi ) via Fe(v ) in ethanol. Abstract : The kinetics and mechanism of ferrate(iv ), (v ) and (vi ) transformations in water and in polar organic solvents (namely ethanol and tetrahydrofuran) have been investigated by the method of 57 Fe Mössbauer spectroscopy of frozen solutions. Ethanol with a very limited amount of water under an inert atmosphere, significantly slows down the transformation reactions of ferrates(iv andv ) and provides direct proof of the existence of intermediate states. Simultaneously, ethanol is oxidized to caboxylates in the close vicinity of the surface of ferrate crystallites as proven by X-ray photoelectron spectroscopy. On the contrary, any transformation of ferrate(vi ) in pure ethanol (with a very limited amount of water) was not observed. Mössbauer spectroscopy of frozen solutions enabled us to experimentally identify and quantify intermediates of ferrate(iv ) and ferrate(v ) transformations for the first time. Sodium ferrate(iv ) in its tetrahedral form, Na4 FeO4, undergoes a two-step charge disproportionation to Fe(iii ) and Fe(vi ) via a Fe(v ) intermediate without any evolution of oxygen in polar protic and aprotic solvents, specifically 2Fe(iv ) → Fe(iii ) + Fe(v ), and Fe(iv ) + Fe(v ) → Fe(iii ) + Fe(vi ), i.e. in sum 3Fe(iv ) → 2Fe(iii ) + Fe(vi ). Ferrate(v ) (K3 FeO4 ) transforms to Fe(iii ) and Fe(vi ) without any indication of the Fe(iv ) intermediate within the detection limit of the method. In addition to a charge disproportionation reaction proceeding in polar liquids, 3Fe(v ) → Fe(iii ) + 2Fe(vi ), a competitive reduction of Fe(v ) directly to Fe(iii ) accompanied by oxygen evolution takes place in water. Oxygen evolution was also measured for ferrate(iv andvi ) transformations in water, but to a higher and a smaller extent compared to ferrate(v ), respectively. The thermodynamics of the suggested ferrate(iv ) and ferrate(v ) transformation pathways was examined by DFT calculations.